Paper based analytical device modified with nanoporous material for the fluorescent sensing of gliadin content in different food samples - Marin Barroso, Evelyn del Valle (2018)
A novel fluorescent paper based immunosensor for the quantification of gliadin content in different food samples was constructed. The device consists of a paper platform modified with amino functionalized mesoporous material. The nanoporous structure and the aminofunctionality increased the anti-gliadin antibodies immobilization capacity of the sensing surface, conferring high sensitivity to the system. The detection limit reached by the described system allowed us to address the control of gluten free foods, which is extremely important to maintain the food safe consumption by patients with celiac disease, wheat allergy measured by immunoglobulin E, non-celiac gluten intolerance and Dermatitis herpetiformis or Duhring disease. The gliadin determination was performed by applying a noncompetitive immunoassay format, where gliadin present in food samples was recognized by anti-gliadin antibodies immobilized on the mesoporous material and quantified by the addition of anti-gliadin antibody labelled with peroxidase, its substrate: hydrogen peroxide and a mediator: 10-acetyl-3,7-dihydrofenoxacin. This mediator by the action of the enzyme generates resorufin, which was excited by a light emitting diode at 550 nm and emitted a signal at 580 nm. The calibration curve obtained for gliadin exhibited a linear range between 0 and 160 μg Kg−1 and a method detection limit of 0.025 mg Kg−1. The obtained values for relative recovery varied between 98.65% and 102.33% for samples enriched with gliadin. Also, the results suggested that the developed fluorescent paper based immunosensor showed good reproducibility and stability, indicating its applicability for high-sensitive gluten free food control analysis.